Standar Kompetensi Lulusan Pendidikan Agama Kristen Berdasarkan Injil Yohanes - Triyono Surahmiyoto (HUPERETES: Jurnal Teologi dan Pendidikan Kristen, 2021)
Graduate competency standards have been implemented by the government through relevant regulations for all subjects courses at all levels of education. It is necessary to make efforts so that Christian religious education can be organized without losing its essence. One form is his efforts to investigate the competency standards of Graduates of Christian religious education based on the Gospel of John. The goal is to uncover the essence of the standard of competence of Graduates of Christian education. This effort is carried out using hermeneutic methods. As a result, two standard models of competency of religious education graduates were found, namely the standard of competence of religious graduates in the Jewish perspective and the standard of competence of religious graduates in perspective. The implication for the learning of Christian education in Indonesia is to maintain the essence of the substance of Christian religious education, develop proficiency in the presentation of materials especially related to the use of terms and languages, sharpen the skill in observing the environment to create learning opportunities and increase the contribution and active role of educators, learners, parents and the church.Standar kompetensi lulusan sudah diberlakukan oleh pemerintah melalui peraturan yang terkait untuk semua untuk semua mata pelajaran/kuliah pada semua jenjang pendidikan. Perlu upaya agar Pendidikan Agama Kristen dapat diselenggarakan dengan tidak kehilangan esensinya. Salah satu bentuk adalah upayanya menelisik standar kompetensi lulusan Pendidikan Agama Kristen berdasarkan Injil Yohanes. Tujuannya adalah untuk mengungkap esensi standar kompetensi lulusan Pendidikan Agama Kristen. Upaya ini dilakukan dengan menggunakan metode hermeneutik. Hasilnya, ditemukan dua model standar kompetensi lulusan pendidikan agama, yaitu standar kompetensi lulusan agama dalam perspektif Yahudi dan standar  kompetensi lulusan agama dalam perspektif. Implikasinya bagi pembelajaran Pendidikan Agama Kristen di Indonesia  adalah perlu tetap mempertahankan esensi substansi Pendidikan Agama Kristen, mengembangkan kecakapan dalam penyajian materi khususnya berkaitan dengan penggunaan istilah dan bahasa, mempertajam kejelian dalam mengamati lingkungan untuk menciptakan peluang pembelajaran dan meningkatkan kontribusi serta peran aktif pendidik, peserta didik, orang tua dan gereja.